Language and Gender: Differences in the Language of Women and Men in “A Business Proposal” K-Drama - Purnami, Anak Agung Istri Agung Tri; Laksminy, Luh Putu (CV. Ulil Albab Corp, 2024)
Sociolinguistics is a field within linguistics that collaborates with sociology, focusing on the interplay between language and social elements within a community of speakers. This particular study aims to explore the linguistic differences between women and men. The research is titled